Answer:
1.75
Step-by-step explanation:
Good luck hope it's right
Answer:
False
Step-by-step explanation:
A reciprocal is when a whole number fraction is flipped
Therefore the reciprocal of 7 is 1/7
The answer is 4 units. The distance between the two points of B and C is equals 6-4=2, because the y is the same. According to the question, the BC is equals 0.5*B'C'. So the length of B'C' is 2/0.5=4 units.
we are given
![f(x)=x^3+4x^2+7x+6](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E3%2B4x%5E2%2B7x%2B6)
We will use rational root theorem to find factors
We can see that
Leading coefficient =1
constant term is 6
so, we will find all possible factors of 6
![6=\pm 1,\pm 2,\pm 3,\pm 6](https://tex.z-dn.net/?f=6%3D%5Cpm%201%2C%5Cpm%202%2C%5Cpm%203%2C%5Cpm%206)
now, we will check each terms
At x=-2:
We can use synthetic division
we get
![f(-2)=0](https://tex.z-dn.net/?f=f%28-2%29%3D0)
so, x+2 will be factor
and we can write our expression from synthetic division as
![f(x)=x^3+4x^2+7x+6=(x+2)(x^2+2x+3)](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E3%2B4x%5E2%2B7x%2B6%3D%28x%2B2%29%28x%5E2%2B2x%2B3%29)
![f(x)=(x+2)(x^2+2x+3)](https://tex.z-dn.net/?f=f%28x%29%3D%28x%2B2%29%28x%5E2%2B2x%2B3%29)
now, we can find factor of remaining terms
![x^2+2x+3=0](https://tex.z-dn.net/?f=x%5E2%2B2x%2B3%3D0)
we can use quadratic formula
![\mathrm{For\:a\:quadratic\:equation\:of\:the\:form\:}ax^2+bx+c=0\mathrm{\:the\:solutions\:are\:}](https://tex.z-dn.net/?f=%5Cmathrm%7BFor%5C%3Aa%5C%3Aquadratic%5C%3Aequation%5C%3Aof%5C%3Athe%5C%3Aform%5C%3A%7Dax%5E2%2Bbx%2Bc%3D0%5Cmathrm%7B%5C%3Athe%5C%3Asolutions%5C%3Aare%5C%3A%7D)
![x=\frac{-b\pm \sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%5Cpm%20%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
we can compare our equation with quadratic equation
we get
![a=1,b=2,c=3](https://tex.z-dn.net/?f=a%3D1%2Cb%3D2%2Cc%3D3)
now, we can plug these values
![x=\frac{-2+\sqrt{2^2-4\cdot \:1\cdot \:3}}{2\cdot \:1}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-2%2B%5Csqrt%7B2%5E2-4%5Ccdot%20%5C%3A1%5Ccdot%20%5C%3A3%7D%7D%7B2%5Ccdot%20%5C%3A1%7D)
![x=-1+\sqrt{2}i](https://tex.z-dn.net/?f=x%3D-1%2B%5Csqrt%7B2%7Di)
![x=\frac{-2-\sqrt{2^2-4\cdot \:1\cdot \:3}}{2\cdot \:1}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-2-%5Csqrt%7B2%5E2-4%5Ccdot%20%5C%3A1%5Ccdot%20%5C%3A3%7D%7D%7B2%5Ccdot%20%5C%3A1%7D)
![x=-1-\sqrt{2}i](https://tex.z-dn.net/?f=x%3D-1-%5Csqrt%7B2%7Di)
so, we get
![x=-1+\sqrt{2}i,\:x=-1-\sqrt{2}i](https://tex.z-dn.net/?f=x%3D-1%2B%5Csqrt%7B2%7Di%2C%5C%3Ax%3D-1-%5Csqrt%7B2%7Di)
so, we can write factor as
![x^2+2x+3=(x-(-1+\sqrt{2}i))(x-(-1-\sqrt{2}i))](https://tex.z-dn.net/?f=x%5E2%2B2x%2B3%3D%28x-%28-1%2B%5Csqrt%7B2%7Di%29%29%28x-%28-1-%5Csqrt%7B2%7Di%29%29)
so, we get completely factored form as
...............Answer